Puncak Peradaban Profetik Masa Rasulullah SAW - Yusri Kombih; Paiman (LP2M Universitas PTIQ Jakarta, 2016)
In terms of religion, Muhammad SAW., is a big name that is not rivaled by anyone in all their roles and existence. Likewise on the historical side of human civilization. The existence of Muhammad was not only as good as the greatest humans, prophets and messengers of all time, but in his time was the culmination of prophetic civilization. This paper describes the peak of the prophetic civilization that existed during the time of Muhammad. In his time, the intensity of the relationship between heaven and earth always occurred, the idealism of all the events on earth occurred and the peak of prophetic civilization necessitated itself. So that period is the best period, the most ideal period, and the peak of human prophetic civilization is.